Physicochemical Quality Changes of Strawberries Stored in Active Packaging Incorporated with Ethylene, Humidity and Oxygen Scavengers at Ambient Temperature (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Strawberry (Fragaria x ananassa) possesses high economic value but is highly perishable due to its soft texture and high moisture content. Active packaging (AP) technology serves as an innovative solution to extend the shelf life of horticultural products by controlling the internal conditions of the package. This study evaluates the effectiveness of AP containing KMnO4 as an ethylene scavenger, vitamin C as an oxygen scavenger, and silica gel as a humidity absorber on the physical and chemical quality of strawberries during storage at room temperature. The experimental design used a 2 x 2 x 3 factorial Completely Randomized Design with five replications. The treatment factors comprised KMnO4 (0 and 60 mg/mL), vitamin C (0 and 0.4 mg/mL), silica gel (0, 5, and 10 g/sachet). Visual observations indicated a significant decline in quality after the seventh day of storage, characterized by softened texture, darkening of the skin color, and the emergence of Botrytis cinereal mold due to high humidity. In the single-treatment test, the application of 5 g of silica gel was the most effective in minimizing the decrease in oBrix values of 4.58%. Meanwhile, the combination of 60 mg/mL KMnO4, 0 mg/mL vitamin C and 5 g of silica gel yielded the best results with a oBrix value of 4.90%, and 0 mg/mL KMnO4, 0 mg/mL vitamin C, and 5 g silica gel was capable of inhibiting the decline of vitamin C content during 7 days of storage. None of the treatments significantly influenced total sugar, free acid, sweetness levels, or vitamin C content, as the high rates of respiration and transpiration at room temperature triggered rapid fruit degradation.